1981
DOI: 10.1093/ageing/10.2.119
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ferritin and Ageing

Abstract: The level of serum ferritin of 226 selected subjects, aged 20 to 93, showed an age-related tendency to rise and in every age studied it was higher in males than in females. This finding is considered to be a consequence of the activation of the reticuloendothelial system and of the increase of iron storage with ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…Depending our findings, serum ferritin concentrations were found similar in all groups, although serum transferrin levels of the ACD and IDA groups were significantly different when compared with the healthy controls. Serum levels of ferritin increases in chronic disorders and in malignancy which are more frequent in elderly (Loria et al 1979) and also has tendecy to increase with age (Casale et al 1981;Witte 1991). However, acute phase responses make the interpretation of the laboratory data difficult, given that both serum ferritin and serum transferrin are acute phase reactants, the former increases and latter decreases in acute inflammation (Leggett et al 1990;Coenen et al 1991;Witte 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Depending our findings, serum ferritin concentrations were found similar in all groups, although serum transferrin levels of the ACD and IDA groups were significantly different when compared with the healthy controls. Serum levels of ferritin increases in chronic disorders and in malignancy which are more frequent in elderly (Loria et al 1979) and also has tendecy to increase with age (Casale et al 1981;Witte 1991). However, acute phase responses make the interpretation of the laboratory data difficult, given that both serum ferritin and serum transferrin are acute phase reactants, the former increases and latter decreases in acute inflammation (Leggett et al 1990;Coenen et al 1991;Witte 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In menopausal women, serum ferritin in creases to a value slightly inferior to that of men [4,7,8,26], Moreover, several authors, performing post-mortem examinations, have observed that hepatic stores of women were obviously greater after menopause [5,6,24], In this study, women have been given iron intakes theoretically sufficient to cover their losses. 1 month of iron supplementa tion improved their iron status.…”
Section: Discussionmentioning
confidence: 79%
“…Menstruating women's serum ferritin val ues are 2 or 3 times lower than those of men, indicating a difference in size of hepatic iron stores between men and women [1,4,8,19,20,26,31]. This difference and the great prevalence of iron deficiency in menstruating women point out the problem of serum ferri tin reference values and of the definition of normal iron stores in menstruating women.…”
Section: Discussionmentioning
confidence: 99%
“…Previously published reports have used serum ferritin levels to diagnose IDA, but the cutoff levels were different in the various studies. The interpretation of the serum ferritin level in older adults is sometimes complicated because its level increases with age and with concomitant chronic illnesses [5, 6]. Therefore, we measured the soluble transferrin receptor (sTfR), which is not influenced by ageing or chronic diseases [7, 8], and we calculated the ratio of sTfR to the log ferritin level (sTfR-F index) to make the test more specific.…”
Section: Introductionmentioning
confidence: 99%